Vehicle Design Processes (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents the current status of research activities concerning vehicle design processes. The design of vehicles is one of the most challenging tasks in engineering because of several reasons. The enormous consumer expectations as well as the intensive global competition aggravates vehicle design. Cost-driven design is a necessity and vehicles need to be economical in production, operation, and recycling; in fact, sustainable design is also imperative for ecological vehicles. The dynamics of vehicles have to be considered in the design of all components and light-weight design is of fundamental importance. Consumers expect convincing functional performance, high product quality, appealing appearance, high reliability, interconnected functionality as well as comprehensible and appealing user interfaces. More and more, additional services are connected to vehicles. These enormous requirements lead to complex multi-domain design processes of vehicles because most of the important decisions are made in the design phase. Production optimization and intelligent operation are important topics, but flaws and insufficiencies in the design stage lead to enormous expenditures in later stages and less-than-perfect products. The design processes of vehicles involve thousands of engineers are spread globally and need to consider multiple product versions and variants as well as multi-company product platforms.